Do Islamic cryptocurrency and Bitcoin co-move at different investment horizons? - Hosen, Mosharrof; Thas Thaker, Hassanudin Mohd; Uddin, Mohammad Nazim; Qoyum, Abdul; Taghizadeh-Hesary, Farhad (https://www.emerald.com/imefm/issue, 2025)
Cryptocurrencies, which have been popular since 2009, raise concerns among investors, researchers and professionals. Amid global economic, financial and health crises, uncertainty has surged, leading investors to seek risk reduction and portfolio diversification. While some critique conventional fiat-based cryptocurrencies, others propose asset-backed alternatives. However, the impact of Shari’ah law-based cryptocurrencies on equity market returns remains largely unexplored in existing literature. This study aims to investigate the lead/lag relationship of selected Islamic and conventional cryptocurrencies from ASEAN and global perspectives. The authors collected daily data of Bitcoin, Ethereum, X8X (Islamic cryptocurrency), Cardano (Islamic cryptocurrency), S&P500, Volatility Index, Economic Policy uncertainty and FTSE Asean Index (from the 4th of November 2019 to the 1st of July 2022) to reveal empirical results through Continuous Wavelet Transform and Correlation Heatmap with Dendrogram. The findings indicate that Bitcoin offers a diversification opportunity for FTSE ASEAN investors for the long-term horizon while S&P500 investors will benefit from short-term investment. On the other hand, Ethereum provides better investment opportunities for both indices in the short run compared to long run. Cardano and X8X offer better investment opportunities in the long run for S&P500 and FTSE ASEAN investors. Interestingly, to check the robustness, the authors used correlation Heatmap based on Dendrogram which provided almost similar results. This study contributes fresh insights to the existing literature concerning cryptocurrency due to the inconclusive findings of past studies, investors are curious to know the impact of cryptocurrency on stock market return from a global perspective which is extensively overlooked, and whether there is any difference between Islamic and conventional cryptocurrency. Therefore, by investigating the abovementioned timely demand issue, this study substantially contributes to the body of cryptocurrency literature.